The influence of critical success factors on business intelligence net benefits - De Jager, Tiaan (Department of Information Systems, 2018)
Background: Business intelligence (BI) is regarded as a key practice to invest into and adopt. This is due to the benefits that can be realized from BI. Critical success factors (CSFs) need to be managed appropriately for organizations to realize maximum benefit from their BI investments. Objective: The objective of this study is to measure the influence of BI CSFs on BI net benefits. In addition, the interrelationships between these CSFs will be measured, the effect of moderating variables will be determined and the reasons why these CSFs are important will be explored. Method: A deductive approach was followed. A conceptual model was derived from literature. This model was used to construct an online survey. The data gathered from the survey was analysed using statistical techniques. The results from the statistical analysis were validated and expanded on by conducting semi-structured interviews with participants who completed the online survey. Results: The results found that top management support, alignment between BI and business objectives and BI technology fit for the business were determined to be the most influential BI CSFs to realize BI net benefits. Top management support was shown to have a relationship with all other CSFs. Well-defined user requirements and user participation did not have a relationship with BI net benefits. Industry and size moderated a small portion of the relationships between BI CSFs and BI net benefits. Conclusion: Organizations need to prioritize top management support, alignment between BI and business objectives, BI technology fit for the business, incremental project management methodology and adequate team skills, to realize BI net benefits. Special attention should be given to top management support as it influences all other BI CSFs.